2014
DOI: 10.1016/j.eurpsy.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

The neurobiology of autism spectrum disorders

Abstract: Data is progressively and robustly accumulating regarding the biological basis of autism. Autism spectrum disorders (ASD) are currently considered a group of neurodevelopmental disorders with onset very early in life and a complex, heterogeneous, multifactorial aetiology. A comprehensive search of the last five years of the Medline database was conducted in order to summarize recent evidence on the neurobiological bases of autism. The main findings on genetic influence, neuropathology, neurostructure and brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 124 publications
1
57
0
1
Order By: Relevance
“…In recent genetic studies, it has been suggested that there is an increased risk of autism with proteins related to synapse formation (23). UPS was considered important for regulating synaptic protein functions, particularly in the synapse.…”
Section: Discussionmentioning
confidence: 99%
“…In recent genetic studies, it has been suggested that there is an increased risk of autism with proteins related to synapse formation (23). UPS was considered important for regulating synaptic protein functions, particularly in the synapse.…”
Section: Discussionmentioning
confidence: 99%
“…Both of HVA and LVA channels control the passive flow of Ca 2+ across membranes. Therefore, alteration in their components leads to defective channel function that translates themselves into a variety of neurological disorders including hemiplegic migraine, episodic and spinocerebellar ataxia, epilepsy, and ASD (Bidaud, Mezghrani, Swayne, Monteil, & Lory, 2006; Breitenkamp, Matthes, & Herzig, 2015; Heyes et al., 2015; Parellada et al., 2014; Stary et al., 2008; Zamponi, 2016). …”
Section: Reviewmentioning
confidence: 99%
“…Evidence has shown that NLGN3 could function in neuron synaptogenesis, and may also connect glia and neurons (Varoqueaux et al 2006;Gilbert et al 2001). Synapse formation of abnormal specification along with communication defects between glia and neurons are intricately linked to autism, a neurodevelopmental disorder with a strong genetic predisposition (Parellada et al 2014;Zeidán-Chuliá et al 2014). Previously, genetic mutations of NLGNs, which cause protein truncation or amino acid substitution, have been identified in autistic individuals (Jamain et al 2003;Zhang et al 2009).…”
Section: Introductionmentioning
confidence: 98%